Fad, Food, or Feed: Alternative Seafood and Its Contribution to Food Systems - Marwaha, Nisha; Beveridge, Malcolm C. M.; Phillips, Michael J. (Frontiers in Sustainable Food Systems, 2022)
Aquatic foods, or “seafood”, are an integral part of the global food system that contribute significantly to many dimensions of human wellbeing, including livelihoods and food and nutrition security. Fish, molluscs, crustaceans, algae and other aquatic foods are of particular importance in low- and middle-income countries as a source of employment, income, and nutrition for many poor and vulnerable people, including women. Global concern over the ability of fisheries and aquaculture to sustainably meet future seafood demand is driving improvements in technology and management. It has also inspired the emergence of plant-based and cell-based seafood, collectively termed “alternative seafood”. Growing investment, consumer demand, and participation by major food companies in the alternative seafood sector necessitate an evaluation of potential opportunities and challenges alternative seafood poses to food systems. This paper explores key economic, social, and environmental implications associated with production, distribution, and consumption of alternative seafood and its interactions with fisheries and aquaculture over the next decade, with specific emphasis on low- and middle-income countries. Available data on current supply and projected growth suggest that alternative seafood may account for almost eight percent of global seafood supplies destined for human consumption in 2030. Assuming current production techniques and expected technological development, the sector has potential for reduced environmental impacts relative to the existing fisheries and aquaculture sectors. However, its potential to impact livelihoods, food and nutrition security, and the environment remains largely a matter of conjecture due to the lack of robust data. Mechanistically, it is believed that growth of alternative seafood supplies will lessen demand for “conventional” seafood and/or meat, a scenario with implications for livelihoods, food and nutrition security, and the environment. Such changes are contingent on technological development, human and institutional behavior, market forces, and ecological linkages and as such, remain speculative. Nevertheless, as a novel sector, new food, and potential alternative to conventional seafood and/or meat, society has an opportunity to shape the growth of alternative seafood and its contribution to national and global development goals. This paper identifies knowledge gaps that require further research to inform inclusive, equitable, and sustainable development and governance of the emerging alternative seafood sector.